2022
DOI: 10.1186/s12979-022-00288-7
|View full text |Cite
|
Sign up to set email alerts
|

Depression, aging, and immunity: implications for COVID-19 vaccine immunogenicity

Abstract: The aging process can have detrimental effects on the immune system rendering the elderly more susceptible to infectious disease and less responsive to vaccination. Major depressive disorder (MDD) has been hypothesized to show characteristics of accelerated biological aging. This raises the possibility that depressed individuals will show some overlap with elderly populations with respect to their immune response to infection and vaccination. Here we provide an umbrella review of this literature in the context… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 180 publications
0
13
0
Order By: Relevance
“…43 In addition, depression requires careful observation because it increases the risk of complications after COVID-19 infection and reduces the immunogenicity of the vaccine. 44 Although the detailed feature and laboratory results of chest discomfort from this study were difficult to determine, the mRNA vaccine promotes the release of inflammatory cytokines, causing cardiovascular disorder. 45 Cardiovascular disorders such as myocarditis and acute myocardial infarction, including chest discomfort, can lead to SAEs after vaccination.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…43 In addition, depression requires careful observation because it increases the risk of complications after COVID-19 infection and reduces the immunogenicity of the vaccine. 44 Although the detailed feature and laboratory results of chest discomfort from this study were difficult to determine, the mRNA vaccine promotes the release of inflammatory cytokines, causing cardiovascular disorder. 45 Cardiovascular disorders such as myocarditis and acute myocardial infarction, including chest discomfort, can lead to SAEs after vaccination.…”
Section: Discussionmentioning
confidence: 89%
“…A study reviewing 11 psychiatric reaction case reports after COVID‐19 vaccination found that altered mental status, mania, depression, and functional neurologic disorder were reported 43 . In addition, depression requires careful observation because it increases the risk of complications after COVID‐19 infection and reduces the immunogenicity of the vaccine 44 . Although the detailed feature and laboratory results of chest discomfort from this study were difficult to determine, the mRNA vaccine promotes the release of inflammatory cytokines, causing cardiovascular disorder 45 .…”
Section: Discussionmentioning
confidence: 99%
“…As the immune system ages, it undergoes senescence that may lead to a diminished response to vaccines (59). These alterations result in impaired immune functions, including limited germinal center responses, reduced numbers of naive cells, ampli ed memory cell populations, and increased in ammatory subsets of adaptive immune cells (60-63).…”
Section: Discussionmentioning
confidence: 99%
“…The activation of the immune inflammatory cells may occur due to the microbial dysbiosis [ 14 ], but also due to the disturbed proteostasis, leading to an accumulation of misfolded proteins and cellular debris [ 15 ]. These fragments of cellular garbage may serve as ligands for certain pattern recognition receptors initiating pro-inflammatory signaling [ 16 ]. Thus, in combination with other contributing factors, both immunosenescence and inflammaging may lead to a poorer antiviral immune response and disturbed viral clearance and also to an increased risk of immune dysregulation [ 9 ].…”
Section: The Impact Of Immunosenescence and Inflammaging On The Immun...mentioning
confidence: 99%
“…The substantial sites of CMV localization were found in the brainstem, diencephalon, and basal ganglia [ 124 ], suggesting that CMV may itself or in combination with SARS-CoV-2 be responsible for CNS damage. Other studies found a depression-specific association of CMV with a reduced resting-state connectivity, white matter integrity, and gray matter volumes [ 125 127 ], indicating that CMV may induce structural and functional brain changes to a greater extent in elderly people with depression [ 16 ]. Thus, it is conceivable that a CMV infection may contribute to long COVID pathology by supporting immunosenescence, neuroinflammation, and by triggering persistent neurological symptoms, particularly in the older population.…”
Section: Potential Mechanisms That May Contribute To Long Covidmentioning
confidence: 99%